2021
DOI: 10.1017/s1092852921000262
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing and treating major depressive episodes that lie along the mood disorders spectrum: focus on depression with mixed features

Abstract: Learning ObjectivesAfter completing this activity, you should be better able to:• Advocate the need to screen all patients with symptoms of depression for even subtle signs of (hypo)mania • Implement evidence-based treatment strategies for patients with depressive episodes with mixed features Accreditation and Credit Designation StatementsThe Neuroscience Education Institute (NEI) is accredited by the Accreditation Council for Continuing Medical Education (ACCME) to provide continuing medical education for phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…The findings of this study offer clinical and research insights for the future. First, the current findings provide evidence that depression should be treated as a spectrum rather than as separate categories focusing on the absence or the presence of a full-blown disorder (Benvenuti et al, 2015 ; Bowins, 2015 ; McElroy et al, 2021 ). Studies have shown that depressed mood and irritability are among the most frequent symptoms of subthreshold depression and major depression across studies (Fava et al, 2010 ; Wesselhoeft, Heiervang, Kragh-Sørensen, Juul Sørensen, & Bilenberg, 2016 ) and that depressed mood may be optimal for predicting future major depression arising from subthreshold depression (Cuijpers, Beekman, Smit, & Deeg, 2006 ; Van Voorhees et al, 2008 ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The findings of this study offer clinical and research insights for the future. First, the current findings provide evidence that depression should be treated as a spectrum rather than as separate categories focusing on the absence or the presence of a full-blown disorder (Benvenuti et al, 2015 ; Bowins, 2015 ; McElroy et al, 2021 ). Studies have shown that depressed mood and irritability are among the most frequent symptoms of subthreshold depression and major depression across studies (Fava et al, 2010 ; Wesselhoeft, Heiervang, Kragh-Sørensen, Juul Sørensen, & Bilenberg, 2016 ) and that depressed mood may be optimal for predicting future major depression arising from subthreshold depression (Cuijpers, Beekman, Smit, & Deeg, 2006 ; Van Voorhees et al, 2008 ).…”
Section: Discussionmentioning
confidence: 78%
“…Under the current diagnostic systems, the classification of depressive disorders is categorical (Uher, Payne, Pavlova, & Perlis, 2014 ). However, researchers have proposed a dimensional approach in which depressive disorders are considered to exist along a spectrum of increasing severity (McElroy, Guerdjikova, & Romo-Nava, 2021 ). From the spectrum perspective, individuals who experience clinically relevant depressive symptoms that do not meet the diagnosis criteria for major depression could be diagnosed with minor or subthreshold depression (Kroenke, 2017 ; Rodríguez, Nuevo, Chatterji, & Ayuso-Mateos, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…A rising amount of research has called for psychiatric disorders, including depressive disorders, to be viewed as a spectrum rather than categorically (Bakker, 2019; Krueger et al, 2018; Noyes et al, 2022). From the spectrum perspective, depressive disorders are acknowledged to exist along a spectrum of increasing severity (McElroy et al, 2021). Therefore, subthreshold depression might be a suitable model for understanding the pathophysiological mechanisms of depression, contributing to the development of tailored treatments for patients at different stages of depression.…”
Section: Introductionmentioning
confidence: 99%
“…From the spectrum perspective, depressive disorders are acknowledged to exist along a spectrum of increasing severity (McElroy et al, 2021). Therefore, subthreshold depression might be a suitable model for understanding the pathophysiological mechanisms of depression, contributing to the development of tailored treatments for patients at different stages of depression.…”
mentioning
confidence: 99%
“…These percentages are significantly increased when a lower number of symptoms is considered [5][6][7]. Yet, despite its clinical relevance, subthreshold hypomania in patients with an ongoing MDE poses several issues in terms of psychopathological characterization, classification, diagnosis, and treatment [8,9]. In 2013, the Diagnostic and Statistical Manual for Mental Disorders, Fifth Edition (DSM-5) [10] introduced the "with mixed features specifier" (MFS), applicable to manic, hypomanic and MDEs, both in bipolar disorder (BD) type I and II and in Major Depressive Disorder (MDD).…”
Section: Introductionmentioning
confidence: 99%